Flame-spray-made Zn-In-O alloyed nanoparticles for NO2gas sensing - T. Samerjai (2018)
© 2016 Elsevier B.V. All rights reserved. In this work, Zn-In-O nanoparticles with different Zn metallic contents (100·Zn/(Zn + In)) were produced by one-step flame spray pyrolysis technique and systematically characterized for NO2sensing. Structural characterizations by x-ray diffraction, transmission and scanning electron microscopy indicated that Zn and In form solid-solution oxide with smaller particle size and lower crystallinity compared with undoped ZnO and In2O3ones. In addition, energy-dispersive and X-ray photoemission spectroscopic analyses revealed that materials prepared with Zn content of 25% and 33% were In-rich oxides while those prepared with Zn contents of 40% and 50% were actually Zn-rich oxides. From gas-sensing measurement, only Zn-In-O sensors with the 50% input Zn content showed improved NO2response while other Zn-In-O sensors displayed inferior performances compared with undoped In2O3sensors. The roles of Zn content on NO2-sensing mechanisms of Zn-In-O sensor were explained based on particle/grain size and doping effects of solid-solution oxide. The Zn-In-O oxide with 50% input Zn content exhibited the optimal sensor response of 1476 to 5 ppm NO2at 250 °C. In addition, it still had good responses of 17 to low NO2concentrations of 0.125 ppm and good selectivity against NO, H2, H2S and CO. Therefore, the flame-made Zn-In-O sensor is another promising candidate for sensitive and selective NO2detections.